Liturgiese sang op die kruispad tussen tradisie en vernuwing - WML Strydom (Acta Theologica)
The renewal of liturgical singing has become an important issue in the Afrikaans-speaking reformed churches. In the process of renewal the theological essence and the ecumenical character of Christian liturgy should be kept in mind, as well as the present cultural shifts in the South African community, which include secularization and the post-modem outlook on life. A well-founded insight in the following aspects will secure a sound balance between tradition and renewal in a present day liturgical theology and practice: the historical background of the relationship between liturgy and singing, the liturgical function of singing, liturgical communication through singing, as well as a hymnological aesthetics and liturgical ethics.